2016
DOI: 10.1080/1059924x.2016.1179239
|View full text |Cite
|
Sign up to set email alerts
|

United Airway Disease Among Crop Farmers

Abstract: Although there are observed relationships between agriculture and respiratory health problems, little attention has been given to relationship between lower and upper airway problems among farmers in the United States. The objective was to investigate the possible relationship between occupational risk factors and "united airway disease" among farmers in eastern North Carolina. Farmers and farm workers were selected from eastern North Carolina by using a cluster sampling method. A total of 180 farmers and farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Although this is lower than the rhinitis prevalence reported among workers in other settings, the positive association between pesticide application and lifetime allergic rhinitis in this study corroborates previous reports (Akpinar-Elci et al 2016; Chatzi et al 2007; Slager et al 2009, 2010; Ye et al 2013). Although we did not evaluate the association of rhinitis with the use of specific pesticides, Slager et al previously reported that exposure to petroleum oil, herbicides 2,4-dichlorophenoxyacetic acid (2,4-D) and glyphosate, the insecticide diazinon, and the fungicide benomyl were positively associated with current rhinitis (Slager et al 2009, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although this is lower than the rhinitis prevalence reported among workers in other settings, the positive association between pesticide application and lifetime allergic rhinitis in this study corroborates previous reports (Akpinar-Elci et al 2016; Chatzi et al 2007; Slager et al 2009, 2010; Ye et al 2013). Although we did not evaluate the association of rhinitis with the use of specific pesticides, Slager et al previously reported that exposure to petroleum oil, herbicides 2,4-dichlorophenoxyacetic acid (2,4-D) and glyphosate, the insecticide diazinon, and the fungicide benomyl were positively associated with current rhinitis (Slager et al 2009, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of self-reported allergic rhinitis among grape farmers was 45.8% (Chatzi et al 2005), and among European greenhouse flower and ornamental plant growers was 31% (Riu et al 2008). Lower prevalence of rhinitis has been reported among farmers and farm workers in East North Carolina (1.1%), and Dutch (7.6%) or Italian swine breeders (13.9%) (Akpinar-Elci et al 2016; Brouwer et al 1986; Galli et al 2015). These differences can be explained, in part, by differences in study methods, e.g., use of information on either self-reported symptoms or physician diagnosis of rhinitis (Akpinar-Elci et al 2016), symptoms and physician diagnosis of hay fever (Slager et al 2009, 2010), or combining questionnaire data with results of allergy test results or specific IgE blood levels (Chatzi et al 2005; Galli et al 2015; Rimac et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…However, these authors and others have cited that underreporting of occupational diseases is likely prevalent, and incidences of occupational respiratory diseases may be much higher than reported. Similarly, an investigation into the associations between farming and “united airway disease” in eastern North Carolina identified that while 35% and 66% of farmers/workers reported lower and upper airway symptoms, respectively, only 1% and 7% of the farmers had a physician diagnosis of rhinitis or asthma, respectively [50]. Furthermore, there was a significant association between upper and lower airway diseases in these farmers/workers; authors argue that considering this “united airway disease” may lead to improved early diagnosis and treatment options to prevent airway health problems in agriculture workers.…”
Section: Asthma/allergic Rhinitismentioning
confidence: 99%
“…Notwithstanding this limitation, 6 of the 43 studies lacking cross‐tabulation (plus all four studies lacking objective pulmonary function tests) provided partial associational data, in which either: 1) the proportion of (presumed) occupational rhinitis cases developing occupational asthma (or vice versa) is reported (albeit in the absence of background rates); or 2) the sequence of development of nasal and chest symptoms are tabulated. Individual study characteristics of excluded studies, including study designs, principal exposure(s), health endpoint(s), number of subjects, and measure(s) of effect appear in Supplemental Tables S1‐S4. Briefly summarizing relevant data from these excluded studies, among workers undergoing objective pulmonary function testing, more than half of those diagnosed with occupational asthma to diphenylmethane diisocyanate (MDI), lupin ( Lupinus angustifolius ) flour, or ammonium persulfate (eg, hairdressers) also gave histories consistent with occupational rhinitis .…”
Section: Resultsmentioning
confidence: 99%
“…While not the object of systematic surveillance in most countries, occupational rhinitis has increasingly been recognized as a significant source of morbidity in the workplace, particularly in such high‐risk occupations as bakers and animal handlers . Furthermore, the frequent coexistence of rhinitis and asthma in the general population has given rise to the so‐called “united airway disease” hypothesis (in which inflammation in the upper and lower airways is seen as pathophysiologically linked) . In the context of the workplace, a corollary question is: “Does occupational rhinitis lead to (or predict the development of) occupational asthma?”…”
Section: Introductionmentioning
confidence: 99%